Tracking Magma Storage: New Perspectives From 40 Years (1980–2020) of Ground Deformation Source Modeling on Etna Volcano - Bonaccorso, Alessandro; Aloisi, Marco (Frontiers in Earth Science, 2021)
Mt. Etna volcano is characterized by a lively eruptive activity with frequent major flank eruptions that can be both purely effusive and explosive-effusive. This volcano has been monitored over 40 years by ground deformation measurements. The studies and modeling of the eruptive processes through these data have mainly concerned single eruptions and the recharge phases that preceded them. In this study, for the first time, we present four decades of numerous recharge periods modeled over time by using the same typology of measurements (geodetic baselines) and the same modeling method. This uniform approach enables tracking the location of magma storage in a robust and unambiguous way during its recharging, which causes the volcano to inflate. In particular, the recharging periods that preceded the main eruptive activities were investigated. The tracking of the source positions contributes to update the representation of the shallow-intermediate plumbing system (last 10 km). Moreover, as a new result, we highlight that the recharges preceding the explosive phases are accompanied by a deepening over time of the centroid of the pressure source. This result opens up new scenarios on the relationship between the position of the recharging storage and the subsequent eruptive style.